Is there a role for melatonin in the treatment of schizophrenia?. Issue 3 (9th August 2022) - Hardman, Stephen; O'Mahony, Elizabeth
Abstract : Schizophrenia can be a severe and debilitating mental disorder with a complex and multifactorial pathophysiology. The neurobiological mechanisms that underpin this illness, alongside other mental disorders, remain elusive. It is recognised that many patients with schizophrenia suffer with disturbed sleep. Here we discuss the role of the physiologically occurring neurohormone, melatonin, in the treatment of sleep disturbances and other symptoms in schizophrenia.